Parkinson S Disease Gene Screening in Familial Cases from Central and South America - Chana-Cuevas, P (John Wiley and Sons Inc, 2024)
Background: Parkinson s disease (PD) is the second most common neurodegenerative disease following Alzheimer s disease. Nearly 30 causative genes have been identified for PD and related disorders. However, most of these genes were identified in European-derived families, and little is known about their role in Latin American populations. Objectives: Our goal was to assess the spectrum and frequency of pathogenic variants in known PD genes in familial PD patients from Latin America. Methods: We selected 335 PD patients with a family history of PD from the Latin American Research Consortium on the Genetics of PD. We capture-sequenced the coding regions of 26 genes related to neurodegenerative parkinsonism. Of the 335 PD patients, 324 had sufficient sequencing coverage to be analyzed. Results: We identified pathogenic variants in 41 individuals (12.7%) in FBXO7, GCH1, LRRK2, PARK7, PINK1, PLA2G6, PRKN, SNCA, and TARDBP, GBA1 risk variants in 25 individuals (7.7%), and variants of uncertain significance in another 24 individuals (7.4%) in ATP13A2, ATP1A3, DNAJC13, DNAJC6, GBA1, LRKK2, PINK1, VPS13C, and VPS35. Of the 70 unique variants identified, 19 were more frequent in Latin Americans than in any other population. Conclusions: This is the first screening of known PD genes in a large cohort of patients with familial PD from Latin America. There were substantial differences in the spectrum of variants observed in comparison to previous findings from PD families of European origin. Our data provide further evidence that differences exist between the genetic architecture of PD in Latinos and European-derived populations. © 2024 The Author(s). Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society. © 2024 The Author(s). Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.